A Method for Secondary Ion Mass Spectrometry Measurement of Lithium Isotopes in Garnet: The Utility of Glass Reference Materials. Issue 3 (18th June 2021) - Hoover, William F.; Penniston‐Dorland, Sarah C.; Baumgartner, Lukas P.; Bouvier, Anne‐Sophie; Baker, Don; Dragovic, Besim; Gion, Austin
Abstract : We present a novel method for the measurement of lithium isotopes in garnet utilising glass reference materials and secondary ion mass spectrometry (SIMS). Measured lithium isotopic compositions of natural garnets are heterogeneous, making them unreliable reference materials for in situ determination. However, SIMS lithium isotope measurements of glasses derived from these natural garnets are isotopically identical to their parent garnets and more homogeneous, demonstrating that they can be used as reliable reference materials. To characterise the composition dependence of instrumental mass fractionation (IMF), oxide and silicate powders were used to synthesise custom‐made glass reference materials (CGRMs) with garnet‐equivalent compositions. Results for six CGRMs measured by SIMS show a significant linear relationship between IMF and FeO and MnO contents. Corrections for this compositional IMF result in changes of up to 12‰ within the compositional range explored. Uncertainty in IMF‐corrected SIMS analyses with a 20 μm spot is in the range of 2.5 to 4.5‰, depending on the garnet composition and reference materials used. The method for in situ lithium isotope measurement in garnet by SIMS presented here is highly adaptable, valid across a range of Al‐rich garnet compositions, and yields spatial resolution and precision necessary to address a range of geological applications. Abstract : Key Points A method was developed for in situ measurement of lithium isotopes in natural garnet by SIMS using synthetic glass reference materials at 20 μm spatial resolution. In situ lithium isotope measurements by SIMS of glasses made by melting natural garnet are indistinguishable from their parent garnet. A correction for compositional instrumental mass fractionation due to iron and manganese composition is proposed yielding total uncertainties of 2.5 to 4.5‰.